Evaluation Of Voice Trunking Performance Using AA2 Over ATM Networks - S. Kenshil, Salih Mohamed (2000)
The urgent market needs for an efficient transport mechanism to carry voice traffic over Broadband Integrated Service Digital Networks (B-ISDN). Asynchronous Transfer Mode (A TM) network has been developed to integrate all types of traffic (e.g. voice, data and video) over B-ISDN networks. ATM Adaptation Layer 2 (AAL2) has been designed for efficient transport of voice, fax, and voice-band data traffic over an A TM virtual circuit. AAL2 allows the VBR sources to generate different packet sizes to be packed in an A TM cell, which increases the number of voice channels and decreases the packetization delay. The growing trend of using A TM has also given great impetus to the use of AAL2 in wire-line trunking (e.g. PBX), which provides a good opportunity for multiplexing many voice channels over a single A TM virtual connection. Voice trunking over A TM using AAL2 is the main subject of this thesis. The efficiency of AAL2 for voice transport in ATM networks is evaluated using a simulation approach. Additionally, the performance and capacity of an ATM multiplexer are analysed based on AAL2 technique. The power of AAL2 trunking and multiplexing high number of voice channels over a single ATM virtual connection makes it an efficient layer to support voice traffic with low delay and high efficiency using low bit rate as a reliable compression technique. In this thesis, the comparison between AAL2 and AAL 1 is made in terms of the number of users that can be carried over Tl AThI trunk. Then the focus is shifted to the use of AAL2 to support Voice and Telephony Over ATM (VTOA) networks. The effect of Timer-Composite Unit (Timer-CD) parameter, number of voice channels and voice coding rate on the packing density and link efficiency is further discussed. The results show that ATM cell packetization delay decreases when the number of users increases. Also, the Timer-CD affects the generation of partially filled cells when it is not set properly. Finally, the use of low coding bit rates to support high number of voice channels makes AAL2 a very efficient layer to carry VTOA networks.